Improving Localization Accuracy of Neural Sources by Pre-processing: Demonstration With Infant MEG Data - Clarke, Maggie D.; Larson, Eric; Peterson, Erica R.; McCloy, Daniel R.; Bosseler, Alexis N.; Taulu, Samu (Frontiers in Neurology, 2022)
We discuss specific challenges and solutions in infant MEG, which is one of the most technically challenging areas of MEG studies. Our results can be generalized to a variety of challenging scenarios for MEG data acquisition, including clinical settings. We cover a wide range of steps in preprocessing, including movement compensation, suppression of magnetic interference from sources inside and outside the magnetically shielded room, suppression of specific physiological artifact components such as cardiac artifacts. In the assessment of the outcome of the preprocessing algorithms, we focus on comparing signal representation before and after preprocessing and discuss the importance of the different components of the main processing steps. We discuss the importance of taking the noise covariance structure into account in inverse modeling and present the proper treatment of the noise covariance matrix to accurately reflect the processing that was applied to the data. Using example cases, we investigate the level of source localization error before and after processing. One of our main findings is that statistical metrics of source reconstruction may erroneously indicate that the results are reliable even in cases where the data are severely distorted by head movements. As a consequence, we stress the importance of proper signal processing in infant MEG.